Synchronous Gastric Adenocarcinoma and Diffuse Large B-Cell Lymphoma in the Pelvis: A Rare Case Presentation - Evangelia Pliakou; Dimitra-Ioanna Lampropoulou; Nikolaos Soupos; Gerasimos Aravantinos (Case Reports in Gastrointestinal Medicine)
Multiple primary cancer (MPC) is defined as more than one primary tumour diagnosed at the same patient, either simultaneously or sequentially. Its incidence is low and varies in reporting among medical centers. Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL) while gastric cancer (GC) is the fifth most frequently diagnosed malignancy. The aim of this article is to present a rare case of a female patient who was diagnosed with two synchronous malignancies, an adenocarcinoma of the stomach (SRCC) and an aggressive extranodal NH lymphoma (DLBCL) within 2 months. Given the fact that there is an expanding availability of more sensitive diagnostic and screening methods, we aim to increase surveillance amongst medical doctors and provide valuable information for further systematic analysis and identification of such rare cases of concurrent malignancies.